Outcome mapping for health system integration - Tsasis, Peter; Evans, Jenna; Forrest, David; Jones, Richard Keith (Journal of Multidisciplinary Healthcare)
Health systems around the world are implementing integrated care strat egies to improve quality, reduce or maintain costs, and improve the pa tient experience. Yet few practical tools exist to aid leaders and man agers in building the prerequisites to integrated care, namely a share d vision, clear roles and responsibilities, and a common understanding of how the vision will be realized. Outcome mapping may facilitate st akeholder alignment on the vision, roles, and processes of integrated care delivery via participative and focused dialogue among diverse sta keholders on desired outcomes and enabling actions. In this paper, we describe an outcome-mapping exercise we conducted at a Local Health In tegration Network in Ontario, Canada, using consensus development conf erences. Our preliminary findings suggest that outcome mapping may hel p stakeholders make sense of a complex system and foster collaborative capital, a resource that can support information sharing, trust, and coordinated change toward integration across organizational and profes sional boundaries. Drawing from the theoretical perspectives of comple x adaptive systems and collaborative capital, we also outline recommen dations for future outcome-mapping exercises. In particular, we emphas ize the potential for outcome mapping to be used as a tool not only fo r identifying and linking strategic outcomes and actions, but also for studying the boundaries, gaps, and ties that characterize social netw orks across the continuum of care.